Trends in addiction treatment in Irish prisons using national surveillance data, 2009–2014. Issue 2 (1st March 2019) - Cannon, Aoife; Nally, Fiona; Collins, Anne; Fay, Ronnie; Lyons, Suzi
Abstract : Purpose: Many studies show that incarcerated populations have higher rates of problem drug use than the general population. The purpose of this paper is to analyse trends in addiction treatment demand in prisons in Ireland from 2009 to 2014 using available national surveillance data in order to identify any implications for practice and policy. Design/methodology/approach: National surveillance data on treatment episodes for problem drug and alcohol use from 2009 to 2014, collected annually by the National Drug Treatment Reporting System (NDTRS), were analysed. Findings: In total, 6 per cent of all treatment episodes recorded by the NDTRS between 2009 and 2014 were from prison services. The number of prison service treatment episodes increased from 964 in 2009 to 1, 063 in 2014. Opiates were the main reason for treatment, followed by alcohol, cocaine and cannabis. The majority (94–98 per cent) of treatment episodes involved males (median age of 29 years) and low educational attainment, with 79.5–85.1 per cent leaving school before completion of second level. The percentage of treatment episodes with a history of ever injecting drugs increased from 20.9 per cent in 2009 to 31.0 per cent in 2014. Practical implications: This study can help policy development and service planning in addiction treatment in prison as it provides an insight into the potential needs of incarcerated populations. It also provides a baseline from which to measure any changes in provision of treatment in prison over time. Originality/value: This is the first study to analyse treatment episodes in prison using routine surveillance data in Ireland. Analysis of these data can provide useful information, not currently available elsewhere.